AI in Mobile Health Apps: Transforming Chronic Disease Management - Sridhar Rao Muthineni, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of artificial intelligence (AI) in mobile health (mHealth) applications for chronic disease management. The article examines how AI-powered mHealth apps are revolutionizing healthcare delivery through personalized treatment plans, real-time monitoring, predictive analytics, and virtual health coaching. The benefits of these technologies, including improved patient outcomes, enhanced engagement, cost reduction, and increased accessibility, are discussed in detail. However, we also critically analyze the challenges and limitations facing AI integration in healthcare, such as data privacy concerns, regulatory hurdles, and potential algorithmic biases. Ethical considerations, including informed consent, transparency in AI decision-making, and ensuring equitable access to AI-powered healthcare, are thoroughly addressed. The article concludes by exploring future directions in AI and mHealth, highlighting emerging technologies and the role of big data in advancing precision medicine. Throughout, we emphasize the importance of balancing technological innovation with responsible implementation to ensure that AI-powered mHealth apps can effectively improve the lives of individuals managing chronic conditions while maintaining the essential human element in healthcare delivery.
Keywords: Artificial Intelligence in Healthcare; Mobile Health (mHealth) Applications; Chronic Disease Management; Personalized Medicine; Healthcare Data Analytics